DISTRIBUTION, ECOLOGY AND IMPACT OF RODENTA SPECIES IN KASHKADARYA REGION - Olim Toshtemirugli Tursunov (Galaxy International Interdisciplinary Research Journal, 2022)
The article presents materials on the distribution of nesting colonies, as well as the number and significance in some biocenoses of the Rodentia order in the Kashkadarya region.